'God's Israel' in Galatians 6.16: An Overview and Assessment of the Key Arguments. (October 2016) - Filtvedt, Ole Jakob
The article presents and discusses the main arguments that have been used to argue either that non-Jews are included or excluded from God's Israel. The arguments in favour of the view that non-Jews are excluded focus on: (i) the syntax and translation; (ii) possible influence from a Jewish synagogue prayer; (iii) the combination of the terms 'mercy' and 'Israel'; and (iv) Paul's regular use of the term 'Israel'. The arguments for the view that non-Jews are included in God's Israel are: (i) that non-Jewish members of God's Israel seem to be a possibility in Galatians; (ii) that an exclusively Jewish Israel is theologically impossible in Galatians; (iii) that an exclusively Jewish Israel in Galatians would have been confusing for the addressees; (iv) the fact that Galatians seems to provide insufficient material for deciding which Jews God's Israel is supposed to denote.